Estimating The Value of PT. Hanjaya mandala Sampoerna Tbk. Using the Discounted cash Flow Method - Tadjoedin, Omar Yusuf; Murtaqi, Isrochmani (Journal of Business and Management, 2012)
The success of Sampoerna attracted Philip Morris International Inc. (â€œPMIâ€), which is one of the leading tobaco companies in the world. In May 2005, the majority ownership of Sampoerna was acquired by Philip Morris Indonesia, an affiliate of PMI.In the capital market, the share price of PT HM Sampoerna Tbk. rises after the acquisition. The end of 2005 the share price of HMSP around Rp 8,000 and continued rising until the recent share price of Rp 51,200 in 2012. The author computes intrinsic share value of the company as of 2012.For the purpose of this final project the author will use Discounted Cash Flow method. The result the authorâ€™s computation is an intrinsic value of Rp 43,392 at august of 2012. While the share price in 2012 of PT HM Sampoerna Tbk. in capital market is Rp 51.200. Which mean the current share price of PT HM Sampoerna Tbk. is overvalue.PT HM Sampoerna Tbk. has a minimum portion of shares in capital market. Actually, the current outstanding shares only 2.05% from total shares. Therefore the intrinsic value of the authorâ€™s computation may not represent the share price of the company in total. In author opinion, the acquisitions cause a positive perception in public that increase the share price.Keywords: Â intrinsic share value, discounted cash flow, income approach.